Tinjauan Digital Leadership Dan Digital Transformation Berdasarkan Scoping Review - Alawiah, Enok Tuti; Tukiran, Martinus (STIKOM Tunas Bangsa Pematangsiantar, 2024)
This article aims to conduct a review using Scoping Review in the journal The International Journal of Management Education which is a Q1 Scopus journal. The journals observed were 16 articles. The aim was to determine research trends related to Digital Leadership and Digital Transformation. The Scoping Review method uses PRISMA with steps, namely identifying the problem, searching for literature sources, selecting literature, compiling and producing results, and determining the article. The observation result is that much of the research was carried out in developed countries. Different patterns were found in 2020, 2021, 2022 and 2023 regarding Digital Leadership and Digital Transformation. The research focus is also diverse and reveals many facts about Digital Leadership and Digital Transformation